A pragmatic randomised controlled trial of local corticosteroid injection and physiotherapy for the treatment of new episodes of unilateral shoulder pain in primary care - Hay, E (2003)
Objectives: To compare the long term effectiveness of local steroid injections administered by general practitioners with practice based physiotherapy for treating patients presenting in primary care with new episodes of unilateral shoulder pain. Methods: Adults consulting with shoulder pain were recruited by their general practitioner. Patients were randomly allocated to receive either corticosteroid injections or community based physiotherapy. Primary outcome was self reported disability from shoulder problems at six months. Secondary outcomes included participant's global assessment of change; pain; function; "main complaint"; range of shoulder movement; co-interventions. A study nurse unaware of the treatment allocation performed baseline and follow up assessments. Analysis was by intention to treat. Results: Over 22 months 207 participants were randomised, 103 to physiotherapy and 104 to injection. Prognostic variables were similar between the two groups at baseline. Mean (SD) improvements in disability scores at six weeks were 2.56 (5.4) for physiotherapy and 3.03 (6.3) for injection (mean difference=-0.5, 95% confidence interval (95% CI): -2.1 to 1.2) and at six months were 5.97 (5.4) for physiotherapy and 4.55 (5.9) for injection (mean difference=1.4, 95% CI -0.2 to 3.0). A "successful outcome" (a minimum 50% drop in the disability score from baseline) at six months was achieved by 59/99 (60%) in the physiotherapy group and 51/97 (53%) in the injection group (percentage difference=7%, 95% CI -6.8% to 20.4%). Co-interventions were more common in the injection group during follow up. Conclusion: Community physiotherapy and local steroid injections were of similar effectiveness for treating new episodes of unilateral shoulder pain in primary care, but those receiving physiotherapy had fewer co-interventions.